Strategi Guru PAI Dalam Memberikan Penilaian Terhadap Hasil Belajar Siswa Secara Daring: - Karimatul Ulfah; Maemunah Sa’diyah (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This thesis is the background that SDN Ciomas 4 Bogor is one of the formal educational institutions that implements distance learning so that it requires schools to be able to make this teaching and learning process effective and efficient. Teachers as educators are required to be able to carry out teaching and learning activities through online. With the problems or obstacles that occur in the process of giving value to student learning outcomes in online learning. The goal is to find out what assessment strategies are effective for teachers to use in assessing students. and to find out the obstacles experienced by teachers and students in online learning. The research method used is a descriptive qualitative method. Using a case study approach, which is a method used to collect and analyze data in a particular case. The results showed that the research strategy used by the Class 5 teacher at SDN Ciomas 4 during this online learning was to create a whatsapp group where the assessment activities could run as they should. By using these media, you can get an assessment from various domains such as cognitive, affective, psychomotor. Keywords: Assesment Strategy, Online, Asseement